2023
DOI: 10.1002/pbc.30485
|View full text |Cite
|
Sign up to set email alerts
|

“It's a lot of things”: Household material hardship among Black and Hispanic parents of children with cancer

Abstract: Household material hardship (HMH)—housing, food, transportation, or utility insecurity—is an adverse social determinant of health that is modifiable in the clinical setting. This mixed‐methods, single‐center study explored the experiences of HMH among Black and Hispanic pediatric oncology parents utilizing a single timepoint survey (N = 60) and semi‐structured interviews (N = 20 purposively sampled subcohort). Forty‐four (73%) parents reported HMH. Qualitatively, participants expressed stress, anxiety, and emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…34 Moreover, financial hardship related to a child's death has been associated with parental feelings of loneliness and isolatation, 34 which may result in heightened or prolonged grief. The high rate of HMH in this population and the association between financial hardship and parental social functioning emphasize the need for a standardized approach to screening and access to needed resources for all families both during treatment, as has recently been recommended, 35 Our study findings must be considered within the following limitations. Our response rate (individual, 30%; household, 38%) was likely affected by the early timepoint in bereavement and the comprehensiveness of the survey asking about sensitive EOL topics.…”
Section: Discussionmentioning
confidence: 96%
“…34 Moreover, financial hardship related to a child's death has been associated with parental feelings of loneliness and isolatation, 34 which may result in heightened or prolonged grief. The high rate of HMH in this population and the association between financial hardship and parental social functioning emphasize the need for a standardized approach to screening and access to needed resources for all families both during treatment, as has recently been recommended, 35 Our study findings must be considered within the following limitations. Our response rate (individual, 30%; household, 38%) was likely affected by the early timepoint in bereavement and the comprehensiveness of the survey asking about sensitive EOL topics.…”
Section: Discussionmentioning
confidence: 96%
“…[23][24][25][26] Others have shown that socioeconomic status mediates the association of inferior survival by race/ethnicity in neuroblastoma and is likely due to disproportionate exposure to adverse social determinants of health driven by poverty. [28][29][30] Systematic collection of social determinants of health data, including individual-level familyreported poverty measures (e.g., family income, household material hardship, insurance), primary language, health literacy, and education, can offer insight into drivers of inequities. 31 While these individuallevel data were not available in our dataset, we did explore the relationship between the economic status of county of residence and survival, and we did not find a significant association.…”
Section: Discussionmentioning
confidence: 99%